The use of the h‐index in academic otolaryngology1. (25th July 2012) - Svider, Peter F.; Choudhry, Zaid A.; Choudhry, Osamah J.; Baredes, Soly; Liu, James K.; Eloy, Jean Anderson
Abstract Objective/Hypothesis: The h‐index is an objective and easily calculable measure that can be used to evaluate both the relevance and amount of scientific contributions of an individual author. Our objective was to examine how the h‐index of academic otolaryngologists relates with academic rank. Study Design: A descriptive and correlational design was used for analysis of academic otolaryngologists' h‐indices using the Scopus database. Methods: H‐indices of faculty members from 50 otolaryngology residency programs were calculated using the Scopus database, and data was organized by academic rank. Additionally, an analysis of the h‐indices of departmental chairpersons among different specialties was performed. Results: H‐index values of academic otolaryngologists were higher with increased academic rank among the levels of assistant professor, associate professor, and professor. There was no significant difference between the h‐indices of professors and department chairpersons within otolaryngology. H‐indices of chairpersons in different academic specialties were compared and were significantly different, suggesting that the use of this metric may not be appropriate for comparing different fields. Conclusions: The h‐index is a reliable tool for quantifying academic productivity within otolaryngology. This measure is easily calculable and may be useful when evaluating decisions regarding advancement within academic otolaryngology departments. Comparison of this metric among faculty members from different fields, however, may not be reliable. Laryngoscope, 2013